Caring for Patients with CRF: Rewards and Benefits - Ayman Karkar (International Journal of Nephrology)
Patients with CRF usually progress through different stages before they reach ESRD and require special medical, social and psychological care and support during the pre-ESRD and following renal replacement therapy (RRT). Early referral of patients with CRF has the advantage of receiving adequate management and regular followup, with significant reduction in cardiovascular morbidity and mortality, attending an education program, prepared psychologically, participate in the decision of type of RRT, preemptive kidney transplantation, early creation of dialysis access, and adequate training in selected modality of RRT. During the early stages of commencement of RRT, psychological support and social care with rehabilitation program are mandatory. The degree of involvement and interaction must be individualized according to the needs of patient and type of RRT. A multidisciplinary team is crucial for implementation of a variety of strategies to help staff intervene more effectively in meeting the care needs of CRF patients.